Hardware-in-the-Loop Modeling of an Actively Fed MVDC Railway Systems of the Future - Stefan Milovanovic (IEEE, 2021)
This paper presents an averaged real-time model of an arbitrary size MVDC railway system. In contrast to references already available in the literature, focusing mainly on specific parts of such a railway network (e.g. power converter installed in a locomotive), this paper offers a thorough insight into the modeling of every part belonging to it. Through a set of reasonable assumptions, the concept of a sector is presented allowing for a straightforward synthesis of any MVDC railway network. Thereafter, real-time models of catenaries, rails, trains, as well as power converters supplying the system are presented in a comprehensive manner. Without loss of generality, the system analyzed hereafter represents a 200 km section of a double-track EuroCity line powered by an actively fed electrification system with three transformer-rectifier groups and two modular multilevel converters. The proposed modeling approach was verified on a large-scale hardware-in-the-loop system comprising one RT Box 3, hosting the model of the exemplary railway network, and two modular multilevel converter digital twins relying on the use of industrial ABB PEC800 controllers.